An integrated approach for identifying the efficacy and potential mechanisms of TCM against atherosclerosis—Wu-Zhu-Yu decoction as a case study. (5th October 2022) - Li, Caihong; Chi, Chenglin; Li, Wenjing; Li, Zongchao; Wang, Xinlin; Wang, Minjun; Zhang, Leiming; Lu, Jing; Liu, Rongxia
Abstract: Ethnopharmacological relevance: Atherosclerosis (AS) is a chronic disease that is associated with high morbidity. However, therapeutic approaches are limited. Wu-Zhu-Yu decoction (WZYD) is a well-known traditional Chinese medicine prescription that is traditionally used to treat headaches and vomiting. Modern studies have demonstrated the cardiotonic effects of WZYD. However, whether WZYD can alleviate AS and its underlying mechanisms remain unclear. Aim of the study: This study aims to investigate the antiatherosclerotic efficacy of WZYD and illustrate its potential mechanisms using an integrated approach combining in vivo and in vitro assessments, including metabolomics, network pharmacology, cell experiments, and molecular docking analyses. Materials and methods: In this work, an atherosclerotic mouse model was established by administering a high-fat diet to apolipoprotein-E deficient (ApoE -/- ) mice for twelve weeks. Meanwhile, the mice were intragastrically administered WZYD at different dosages. Efficacy evaluation was performed through biochemical and histopathological assessments. The potential active constituents, metabolites, and targets of WZYD in atherosclerosis were predicted by metabolomics combined with network pharmacology analysis, the constituents and targets were further assessed through cell experiments and molecular docking analysis. Results: WZYD decreased the lipid levels in serum, reduced the areas of aortic lesions, and attenuated intimal thickening, which had antiatherosclerotic effects in ApoE -/- mice. Metabolomics and network pharmacology approach revealed that the ten constituents (6-shogaol, evodiamine, isorhamnetin, quercetin, beta-carotene, 8-gingerol, kaempferol, 6-paradol, 10-gingerol, and 6-gingerol) of WZYD affected 24 metabolites by acting on the candidate targets, thus resulting in changes in five metabolic pathways (sphingolipid metabolism; glycine, serine and threonine metabolism; arachidonic acid metabolism; tryptophan metabolism; and fatty acid biosynthesis pathway). Cell experiments indicated that the ten key compounds showed antiproliferative effects on the vascular smooth muscle cell. Moreover, the key compounds exhibited direct interactions with the key targets, as assessed by molecular docking analysis. Conclusion: This study revealed that WZYD exerted therapeutic effects on atherosclerosis, and the potential mechanisms were elucidated. Furthermore, it offered a powerful integrated strategy for studying the efficacy of traditional Chinese medicine and exploring its active components and possible mechanisms. Graphical abstract: Image 1 Highlights: An integrated approach was performed to analyze the mechanisms of Wu-zhu-yu decoction in atherosclerosis. An atherosclerosis animal model was built, and Wu-zhu-yu decoction was found to be effective. Thirty-three biomarkers of atherosclerosis were identified through metabolomics. Ten constituents in Wu-zhu-yu decoction affected 24 metabolites by acting on PPARG, BCL2, and TNFA targets. The constituents and targets were assessed by cell experiments and molecular docking.